Selecting Dogs for Explosives Detection: Behavioral Characteristics - Lazarowski, Lucia; Waggoner, Lowell P.; Krichbaum, Sarah; Singletary, Melissa; Haney, Pam S.; Rogers, Bart; Angle, Craig (Frontiers in Veterinary Science, 2020)
Detection dogs are widely considered the most effective and adaptive explosives detection technology. Increases in emerging sophisticated threats are accelerating the demand for highly capable explosives detection, causing a strain on available supplies of quality canines worldwide. These strains are further compounded by rigorous behavioral standards required to meet mission-specific capabilities, leading to high rates of dogs disqualified from training or deployment. Ample research has explored the behavioral characteristics important for assistance, guide, and other traditional working roles, while those corresponding to more specialized tasks such as detection of explosives are not as well understood. In this review we aim to identify the behavioral characteristics important for operational tasks of explosives detection dogs, contrasting with that of other working roles and highlighting key differences between explosives and other types of detection dogs. Further, we review the available research on methods for assessing and selecting candidate detection dogs and make recommendations for future directions and applications to the industry. Improvements and standardization in assessment technology allowing for the identification and enhancement of behavioral characteristics will be key to advancing canine detection technology in general.